2017
DOI: 10.1111/bjc.12135
|View full text |Cite
|
Sign up to set email alerts
|

A path model of different forms of impulsivity with externalizing and internalizing psychopathology: Towards greater specificity

Abstract: Objectives A growing empirical literature indicates that emotion-related impulsivity (compared to impulsivity that is unrelated to emotion) is particularly relevant for understanding a broad range of psychopathologies. Recent work, however, has differentiated two forms of emotion-related impulsivity: A factor termed Pervasive Influence of Feelings captures tendencies for emotions (mostly negative emotions) to quickly shape thoughts. A factor termed Feelings Trigger Action captures tendencies for positive and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 97 publications
2
64
0
Order By: Relevance
“…Specifically, a tendency toward impulsive speech and action in response to emotions has been differentiated from a tendency toward cognitive impulsiveness in response to (mostly negative) emotions—for example, rumination after a negative event, or reflexively generalizing from a negative event to the broader sense of self-worth (Carver et al, 2011). Reports of cognitive impulsiveness in reaction to emotion relate more strongly to internalizing syndromes than do other aspects of impulsiveness; reports of behavioral impulsiveness in reaction to emotion relate more strongly to externalizing disorders than do other aspects of impulsiveness (Johnson, Carver, & Joormann, 2013; Johnson, Tharp, Peckham, Carver, & Haase, in press). …”
Section: Internalizing Externalizing and Thought Disordersmentioning
confidence: 93%
“…Specifically, a tendency toward impulsive speech and action in response to emotions has been differentiated from a tendency toward cognitive impulsiveness in response to (mostly negative) emotions—for example, rumination after a negative event, or reflexively generalizing from a negative event to the broader sense of self-worth (Carver et al, 2011). Reports of cognitive impulsiveness in reaction to emotion relate more strongly to internalizing syndromes than do other aspects of impulsiveness; reports of behavioral impulsiveness in reaction to emotion relate more strongly to externalizing disorders than do other aspects of impulsiveness (Johnson, Carver, & Joormann, 2013; Johnson, Tharp, Peckham, Carver, & Haase, in press). …”
Section: Internalizing Externalizing and Thought Disordersmentioning
confidence: 93%
“…Negative urgency has been reported to be one of the strongest indices of pathological status and complications among gamblers (Billieux et al, 2012). Converging studies have explored the neurobiological roots of negative urgency in basic emotion regulation processes (Chester et al, 2016;Ruiz de Lara, Navas, Soriano-Mas, Sescousse & Perales, 2018), and have shown that negative urgency plays a major role in an array of externalizing psychopathologies, including other addictions (Johnson, Carver, & Joorman, 2013;Johnson, Tharp, Peckham, Carver, & Haase, 2017).…”
Section: Gambling and Emotion Regulationmentioning
confidence: 99%
“…[8] Thus, impulsivity is associated with a myriad of negative consequences most notably aggression, antisocial behavior, poor treatment compliance, self-harm, and suicide. [9][10][11] Thus as a clinical construct impulsivity is highly predictive of a poor prognosis thus further emphasizing its clinical relevance.…”
Section: Why Is Impulsivity Important?mentioning
confidence: 99%
“…Recent research has demonstrated a relationship between emotion-focused impulsivity that triggers action and externalizing problems such as aggression and substance use. [11] In regards to internalizing problems, another emotion-focused facet of impulsivity has been found individual's view of the world and their automatic thoughts. [11] Impulsivity is also known to be highly related to self-harm and suicide; a recent meta-analysis demonstrated general support for this ideology demonstrating a relationship between self-injurious behavior, thoughts about self-harm and impulsivity.…”
Section: Why Is Impulsivity Important?mentioning
confidence: 99%
See 1 more Smart Citation